PENGARUH KOMPETENSI, MOTIVASI, KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA, KINERJA PEGAWAI TVRI JAKARTA - ROSSA CARACIOLLA; NURWANTI NURWANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
Abstract : This research aims to determine the effect of competence, motivation, and organization commitment variables on job satisfaction and employee performance in TVRI Jakarta employees. The form of research used is descriptive and causality with a sample size of 84 employees. The technique used to collect data is a questionnaire with a likert scale. The research sample was obtained using purposive sampling method and using Structural Equation Modeling (SEM) analysis method to test the effect of independent variabels on the dependent variable. The result showed that  competence has a effect on job satisfaction and employee performance. Motivation has a effect on job satisfaction and employee performance. Organization commitment has a effect on job satisfaction and employee performance, and job satisfaction has a effect on employee performance, TVRI Jakarta is advised to pay attention to factors that support the improvement of employee competence, motivation and commitment.